The Effect of Self-care Education Based on Self-efficacy Theory, Individual Empowerment Model, and Their Integration on Quality of Life among Menopausal Women - Mahboobeh Kafaei-Atrian; Zohreh Sadat; Saeideh Nasiri; Fatemeh Sadat Izadi- Avanji (Shiraz University of Medical Sciences, 2022)
Background: Menopause has adverse physical and emotional effects on the quality of life. The aim of this study was to determine the effect of self-care education based on self-efficacy theory, individual empowerment model, and their integration on the quality of life among menopausal women. Methods: In this quasi-experimental study, 186 menopausal women, aged 45-60 years at Kashan health centers entered the study using cluster sampling for health centers and simple random sampling inside each center from the list of the population from December 2019 to March 2020. The intervention was performed in 3 groups, using empowerment training, self-efficacy training, and their integration for 4 sessions each lasting 1-1.5 hours of weekly training. Three study groups were selected from different centers to minimize information exchange. Menopausal women's quality-of-life questionnaire was used to assess the quality of life. Questionnaires were completed pre-intervention and one and three months after completing the intervention. SPSS16 softwareand ANOVA, Chi-square, and repeated measure tests were used. Results: The mean±SD score of quality of life in pre-intervention measurement was 32.96±10.62 in empowerment, 31.93±12.54 in self-efficacy, and 34.07±11.7 in integrated groups. The intervention was effective in improving the quality of life of all three groups (P values were Conclusion: This study showed that empowerment and enhancing self-efficacy could improve menopausal women's quality of life. This can help health professionals to better educate postmenopausal women about self-care in menopausal complications.